Aromatic radical perfluoroalkylation reactions - Postigo, Jose Alberto (2012)
This account intends to cover recent literature on radical perfluoroalkylation reactions of aromatic nuclei in organic and aqueous media. Emphasis will be placed on radical aromatic perfluoroalkylation reactions in water or aqueous media, with the aim of exploring aromatic radical reactivity in a benign environment. © 2012 Published by NRC Research Press.